The pressor effect of angiotensin-(1-7) in the rat rostral ventrolateral medulla involves multiple peripheral mechanisms - Rita C. Oliveira; Maria J. Campagnole-Santos; Robson A. S. Santos (Clinics, 2013)
OBJECTIVE: In the present study, the peripheral mechanism that mediates the pressor effect of angiotensin-(1-7) in the rostral ventrolateral medulla was investigated. METHOD: Angiotensin-(1-7) (25 pmol) was bilaterally microinjected in the rostral ventrolateral medulla near the ventral surface in urethane-anesthetized male Wistar rats that were untreated or treated (intravenously) with effective doses of selective autonomic receptor antagonists (atenolol, prazosin, methyl-atropine, and hexamethonium) or a vasopressin V1 receptor antagonist [d(CH2)5 -Tyr(Me)-AVP] given alone or in combination. RESULTS: Unexpectedly, the pressor response produced by angiotensin-(1-7) (16 ± 2 mmHg, n = 12), which was not associated with significant changes in heart rate, was not significantly altered by peripheral treatment with prazosin, the vasopressin V1 receptor antagonist, hexamethonium or methyl-atropine. Similar results were obtained in experiments that tested the association of prazosin and atenolol; methyl-atropine and the vasopressin V1 antagonist or methyl-atropine and prazosin. Peripheral treatment with the combination of prazosin, atenolol and the vasopressin V1 antagonist abolished the pressor effect of glutamate; however, this treatment produced only a small decrease in the pressor effect of angiotensin-(1-7) at the rostral ventrolateral medulla. The combination of hexamethonium with the vasopressin V1 receptor antagonist or the combination of prazosin, atenolol, the vasopressin V1 receptor antagonist and methyl-atropine was effective in blocking the effect of angiotensin-(1-7) at the rostral ventrolateral medulla. CONCLUSION: These results indicate that angiotensin-(1-7) triggers a complex pressor response at the rostral ventrolateral medulla that involves an increase in sympathetic tonus, release of vasopressin and possibly the inhibition of a vasodilatory mechanism.